PREVALENCE OF HYDATIDOSIS AND HEPATIC FASCIOLIASIS IN SLAAT BASRAH ABATTOIRUGHTERED ANIMALS ‘‘ - Esraa Abdul Wadood (Basrah Journal of Veterinary Research)
Astudy on the occurrence ofhydatidosis and liver ﬂuke infection in slaughtered animals was carried out overyear ( l999_200()) at basrah abattiors . the study carried 1851 sheep ,655 cattle and 172 but't'alo. The study showed 134 (7.2%) .55 (8.3% ) and 64(36 . 5 %) had hydatid cyst respectively . the l'requenc_~ ol’ the cyst in lung o3(47.()l°/o) .29(52.72"/o) and 3l (48.4%) in inspected animals (sheep .cattle and bulitalo ) while in liver 7I(52.9%) .36(65.4%) and 33(51.5"/o) respectively also animals had been inspected for hepatic fascioliasis of - 5l(2.75%) .29 (4.42%) and 28 (l(>.2"/o ) respectively . the rate of infection had also been reported according to seasonal variation among the sam species of ammals,the study showed high infection rate with hydatid cyst in sheep.cattlc i ‘md bullill“ '” -“P""lt—’ l~“-3"“"?t) ~ l5.4""0)ilI1"/é») t‘c.~’Pecticl)’.while infection rate with fascioliasis is high in sheep(3.2"/o) and bufl'alo(22.9%) in winter